Implementasi Metode Transportasi North West Corner Untuk Optimasi Biaya Pengiriman Barang Pada UD. Naga Timbul - Hendriyanti, Yurika Cici; Masrizal, Masrizal; Sihombing, Volvo (MEANS (Media Informasi Analisa dan Sistem), 2023)
Delivery of goods or services is an important part of the activities of a government agency or a particular company. The problem that is often faced with shipping is the issue of cost. The delivery system is a series of activities that determine the company where the products are sent to consumers to be marketed with the aim of facilitating product marketing. The delivery system is one of the main supports after the production process thus realizing the optimization of shipping costs. UD. Naga Timbul is a company engaged in the fertilizer sector. Goods produced will be sent to the branch company UD. Naga Timbul. The method in this study is to use the North West Corner (NWC) method to calculate the cost of shipping goods. The application consists of three parts, namely, filling in the data supply and location of demand, as well as filling in data on the cost of shipping goods. To build this system application design, Microsoft Visual Basic 2008 and Mysql software are needed as database creation.